MENGINTIP FEMINISME DAN GERAKAN PEREMPUAN - Faizain, Khoirul (EGALITA, 2007)
Feminist idea has ben existed inEuropeat 18th century and the end of 19th century feminist movement emerged in America. Later, feminist theories grew such as liberal feminist, radical feminist, marxist veminist and socialist feminist. During the growing process of those theories, women movement voiced theirv resistencies that theories may put women on undesirrable position like what was proposed by Eco feminism group in 1980. for moslem world, emancipation discourse is firstly proposed by Syeikh Muhamad Abduh (1849-1905) from Egypt also the prophet Muhammad was the initiator tomstruggle againts any forms ofÂ  inequality. Hence, in moslem world context, holistics social framework should be the movement framework of feminist movement. It may be safely put in this way: â€œit is not about women taking over, but women and men together expressing their full potentials neither superior not inferiorâ€.